Recurrent Thrombotic Thrombocytopenic Purpura-Like Syndrome as a Paraneoplastic Phenomenon in Malignant Peritoneal Mesothelioma: A Case Report and Review of the Literature - Francisco Socola; Arturo Loaiza-Bonilla; Ernesto Bustinza-Linares; Ricardo Correa; Joseph D. Rosenblatt (Case Reports in Oncological Medicine)
We report the case of an African American male with no significant past medical history presenting with recurrent, rapidly relapsing episodes of thrombotic thrombocytopenic purpura (TTP) despite aggressive treatment with several lines of treatment. Incidentally, these episodes were associated with severe abdominal pain which eventually developed into acute abdomen and prompted exploratory laparotomy, revealing diffuse carcinomatosis with a tumor located on the left pelvis that was encasing the distal sigmoid colon. Pathology made a final diagnosis of peritoneal mesothelioma. TTP-like syndrome (TTP-LS) has been described as a paraneoplastic phenomenon in several malignancies but never before in the setting of malignant mesothelioma. Paraneoplastic TTP-like syndrome has historically been associated with a dismal prognosis and particular clinical and laboratory abnormalities described in this paper. It is of utmost importance to make a prompt determination whether TTP is idiopathic or secondary to an underlying condition because of significant differences in their prognosis, treatment, and response. This paper also reviews the current literature regarding this challenging condition.